An Application of Stereo Matching Algorithm for Waste Bin Level Estimation - Islam, Md. Shafiqul; Hannan, M.A; Basri, Hasan (Journal of Asian Scientific Research, 2012)
In this paper, region based stereo matching algorithms are developed for extraction depth information from two colour stereo image pair of waste bin. Depth calculation technique from a disparity map is a key part of this study. A filter eliminating unreliable disparity estimation was used for increasing reliability of the disparity map. Global Error Energy has calculated from the stereo images and smoothing function has developed within the error energy matrix. Depth has calculated from the disparity map. A technique for depth estimation and various application of this algorithm has discussed, various algorithms for depth feature extraction are also discussed. GUI has developed using Matlab for classifying the waste bin. It obtained results by algorithms were presented and compared.